Characterization of Rosculus vilicus sp. nov., a rhizarian amoeba interacting with Mycobacterium avium subsp. paratuberculosis - Jessu, Amélie; Delafont, Vincent; Moyen, Jean-Louis; Biet, Franck; Samba-Louaka, Ascel; Héchard, Yann (Frontiers in Microbiology, 2023)
Free-living amoebae are described as potential reservoirs for pathogenic bacteria in the environment.It has been hypothesized that thisit might be the case for Mycobacterium avium subsp.paratuberculosis, the bacterium responsible for paratuberculosis. In a previous work, we have isolated an amoeba from a water sample in the environment of infected cattle and showed that this amoeba was associated with Mycobacterium avium subsp. paratuberculosis. While aA partial 18S rRNA gene has allowed us to suggest that this amoeba was a Rosculus-like, but at that time we were not able to sub-cultivate it. In the present study, we succeeded in cultivating this strain at 20-25°C. This amoeba is among the smallest (5-7 µm) described. The sequencing of the whole genome allowed us to extract the full 18S rRNA gene and propose this strain as a new species of the Rosculus genus, i.e., R. vilicus.AlsoOf note, the mitochondrial genome is particularly large (184,954 bp). Finally, we showed that this amoeba was able to phagocyte Mycobacterium avium subsp. paratuberculosis and that the bacterium was still observed within amoebae after at least three days. In conclusion, we have characterized a new environmental amoeba species at the cellular and genome level that was able to interact with Mycobacterium avium subsp. paratuberculosis. ThereforeAs a result, R. vilicus is a potential candidate as an environmental reservoir for Mycobacterium avium subsp. Paratuberculosis paratuberculosis but further experiments are needed to test this hypothesis..